Analisis Peran CV Anugerah Alam Mineral Salumalino Terhadap Perkembangan Sosial Ekonomi Masyarakat Desa Bancea Kecamatan Pamona Selatan Kabupaten Poso - Parewa, Jeremi K.N; Walenta, Abdi Sakti; Sangkide, Charis Elfis Fajar; Melumpi, Martho Harry (Fakultas Ekonomi Universitas KristenTentena, 2024)
This research is based on the role of the AMDK industry in community development because it utilizes natural resources in the village such as mountain springs. This research aims to determine and analyze the role of CV. Natural Gift of Salumalino Minerals for the Social and Economic Development of the Bancea Village Community. The method used is descriptive qualitative with data collection techniques using observation, interviews and documentation The research results show that the presence of the AMDK industry, namely CV. Anugerah Alam Mineral Salumalino has an important role in social development both in social organizations of the community and in the social environment of the community as a whole and plays a role in the economic development of the community such as opening up employment opportunities, can minimize the unemployment rate in Bancea Village and can contribute clean water in two aspects, namely Contribution providing free clean water through existing reservoirs and affordable prices for bottled drinking water products for the people of Bancea Village.